Aktivitas Antimikroba Kapang Endofit Dari Tumbuhan Pesisir Sarang Semut (Hydnophytum Formicarum) Hasil Kultivasi - Nurzakiah Nurzakiah; Desniar Desniar; Kustiariyah Tarman (Barakuda'45, 2020)
Seven isolates of endophytic fungi from sarang semut plant (Hydnophytum formicarum) was observed for their antibacterial activity. This study aimed to determine the culture period of sarang semut endophytic fungi that has the best antibacterial activity. Screening of endophytic fungi resulted that RS1A isolate showed the widest zone of inhibition, which was 4.7 mm against Escherichia coli and Bacillus subtilis. The highest antibacterial activity of RS1A was shown by the extracts from static culture harvested on day 21. Zone of inhibition against Escherichia coli was 10 mm at a concentration of 2 mg/well and 7 mm at a concentration of 1 mg/well, while zone of inhibition against Bacillus subtilis was 7 mm and 6 mm, respectively.